(untitled) (Journal of the College of Basic Education, 2022)
Contemporary critical schools represented one of the important topics that worked in the field of the cinematic film, and the semiotic approach is one of these critical approaches, hence the importance of the research in that it deals with the topic of the mark and its movement as a result of the variation in the type of constructive relations between them, which leads to the production of more than one level of meaning. In addition to its importance to scholars in the field of cinematic and television arts, as well as critics and workers in the field of film and television production, the aim of the research will be to reveal the ways in which the mark is transformed to produce meaning in the cinematic film, and the limits of the research will be world cinema, and the intended research sample is the film (PARFUM) .